Innovation of control valve motorization method for regulating turbine rotation in micro hydro generators - Hardi, Supri; Safitri, Nelly; Yaman, Yaman; Radhiah, Radhiah; Jamaluddin, Jamaluddin (International Journal of Applied Power Engineering (IJAPE), 2025)
The method of transferring the main load to the dummy load is still used in micro hydropower plants. Because the turbine and generator are constantly operating at maximum capacity, the load transfer system, also known as the electronic load control (ELC) system, is ineffective and inefficient. The researcher devised a method for controlling the pressure/flow rate on the branch pipe by using a control valve motorized (CVM). Control valve motorized (CVM) is responsible for the opening and closing of branch pipelines using an electric motor. The goal is to achieve voltage and frequency stability by using CVM to adjust the flow/pressure of water in the branch pipe. The method involves designing and testing the CVM system via a Pelton turbine module connected to the generator. The results of testing the Pelton turbine module with a pressure of 4 kg/cm2 on a 34-inch pipe show that the turbine rotates at 800 rpm. Brushless direct current (BLDC) generator with 12 poles and a Pelton turbine. The proportional integral derivative (PID) controller control parameters are calculated by the control system using the Nichols-Ziggler method, with tuning results of PB 130%, Ti 2.8 seconds, and Td 0.7 seconds. A frequency of 50 Hz and a voltage of 61 volts is produced by controlling the set point (SP) at 55% of the process variable (PV) and the manipulated variable (MV) to CVM at 38%, respectively. The conditions are implemented by varying the load on the system by connecting and disconnecting the load; the system remains stable for 5 seconds.